1997
DOI: 10.1108/00251749710176091
|View full text |Cite
|
Sign up to set email alerts
|

When the tourists flew in: strategic implications of foreign direct investment in Vietnam’s tourism industry

Abstract: Emphasizes that tourism forms the largest industry in the world and the Vietnamese Government has targeted it for strategic foreign direct investment (FDI). Notes although researchers and policy makers comprehend particular aspects of tourism, they often misperceive how the variables interact within economic and political systems. Elaborates on experiences in similar and related Asian markets that indicate policies necessary to develop a sustainable, socially and ecologically‐desirable tourism industry through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 4 publications
3
29
0
1
Order By: Relevance
“…The results of this study also suggest that tourism has significant effects on capital investment and are thus aligned with the findings of Ho and Rashid [56] in Malaysia and the Philippines. In addition, capital investment significantly influences tourism development, which is in line with Haley and Haley [57], who suggested that FDI leads to tourism. Tourism development indicates a significant relationship with agriculture; to the best of our knowledge, the literature is silent on the econometric relationship between tourism and agriculture.…”
Section: Resultssupporting
confidence: 78%
“…The results of this study also suggest that tourism has significant effects on capital investment and are thus aligned with the findings of Ho and Rashid [56] in Malaysia and the Philippines. In addition, capital investment significantly influences tourism development, which is in line with Haley and Haley [57], who suggested that FDI leads to tourism. Tourism development indicates a significant relationship with agriculture; to the best of our knowledge, the literature is silent on the econometric relationship between tourism and agriculture.…”
Section: Resultssupporting
confidence: 78%
“…The result clearly shows that there is unidirectional causality running from FDI to ITA with three lags because the p-values (proportionally 0.0295, 0.0618, 0.0205) are significant and less than the 10% percent level. This is the same with previous research, such as Haley and Haley [1997], Tang et al [2007] who found a one-way causal relationship in the direction of FDI to tourism. In addition, we also removed the evidence to describe the relationship between tourism and FDI proven at lag 1 (p value equal to 0.0948).…”
Section: Granger Causality Testing Procedures For Causalitysupporting
confidence: 80%
“…A number of studies from Asian countries show that there is a causal relationship between FDI and tourism, which is supported by the study by Haley and Haley [1997] in the case of Vietnam. International business travel has recently increased as the result of the reinforcement of FDI and it has been argued that this trend has had the tendency to diminish the diversity of cultures, and economic and political structures.…”
Section: Literature Reviewmentioning
confidence: 62%
See 1 more Smart Citation
“…Very few scholars have been working on FDI within the tourism industry. The few existing publications on tourism FDI predominately discuss the motives and particularities of the internationalisation of the hotel industry (Dunning and McQueen, 1981; Dunning and Kundu, 1995; Buckley and Geyikdagi, 1996; Williams and Deslandes, 2008), the overall structure of tourism FDI (Endo, 2006) or the political economy of tourism FDI in specific countries, such as Ghana (Teye, 1988), Greece (Buckley and Papadopoulos, 1988), Turkey (Buckley and Geyikdagi, 1996), Vietnam (Haley and Haley, 1997; Sadi and Henderson, 2001) and Cuba (Colantonio, 2006).…”
Section: Introductionmentioning
confidence: 99%